Mathematical modeling of inclined accretion disks in cataclysmic variables. (October 2020) - Lukin, V V; Shakura, N I; Postnov, K A
Abstract: The work is devoted to synthetic light curves modeling for the observed binary stellar systems and an interpretation of their characteristic features including pre-eclipse humps, asymmetry in the vicinity of the eclipse and variability of light curves from revolution to revolution. The mathematical model of the accretion disk including the radiation cooling of the plasma, gravitational forces and incomplete plasma ionization has been studied. The results of the plasma flows calculation allow one to use the radiated energy for synthetic light curves construction. In a number of simulations the formation of an inclined accretion disk is noted. The inclination may be caused by the instability of the circumstellar plasma flowing around the disk at the initial stages of its formation. The disk obtained in the calculations retrogradely precesses with a period of about 40 orbital periods of the system. Due to this precession in different orbital periods the jet enters the disk in different places. This may explain the significant variability of the light curves of the binary star system as well as the presence of brightness humps at the eclipse.